A concussão ambiental como compreensão à expansão do controle penal da corrupção - Leme, Carolina da Silva (2020)
This dissertation intends to analyze the effectiveness of the modern theories regarding criminal control of corruption in Brasil, in order to analyze if the guidelines adopted today by the Legislative, Executive and Judiciary Powers are, in fact, effective and efficient measures due to the systemic level of corruption reached in Brazil. Thus, based on bibliographic sources, the evolution of the fight against corruption in the world will be analyzed adopting as its main premise the 1990s, when corruption was no longer seen by the United States a market incentive and started to be seen as harmful to the economy, giving way to new laws, treaties and international conventions, as well as modern theories. From this perspective, the present study will analyze the internalization of the treaties, conventions and modern theories of international imputation to the Brazilian scenario under the focus of effectiveness and efficiency for the internal control of corruption, making criticisms that go into the victimological and political-economic scenario. In the end, using a paradigm envisioned by the Italian Criminal Law in the mid-1990s called "Concussione Ambientale", the present study will reach its conclusion through the analysis of the rationalization in the adoption of new mechanisms and the proposition of an intermediate crime, similar to what was proposed in Italy, aiming at the non-liability of victims of systemic corruption, as well as the protection of the internal political-economic scenario